Regulation of mTORC1 Signaling by Src Kinase Activity Is Akt1-Independent in RSV-Transformed Cells - Martina Vojtěchová; Jolana Turečková; Dana Kučerová; Eva Šloncová; Jiří Vachtenheim; Zdena Tuháčková (Neoplasia: An International Journal for Oncology Research, 2008)
Increased activity of the Src tyrosine protein kinase that has been observed in a large number of human malignancies appears to be a promising target for drug therapy. In the present study, a critical role of the Src activity in the deregulation of mTOR signaling pathway in Rous sarcoma virus (RSV)-transformed hamster fibroblasts, H19 cells, was shown using these cells treated with the Src-specific inhibitor, SU6656, and clones of fibroblasts expressing either the active Src or the dominant-negative Src kinase-dead mutant. Disruption of the Src kinase activity results in substantial reduction of the phosphorylation and activity of the Akt/protein kinase B (PKB), phosphorylation of tuberin (TSC2), mammalian target of rapamycin (mTOR), S6K1, ribosomal protein S6, and eukaryotic initiation factor 4E-binding protein 4E-BP1. The ectopic, active Akt1 that was expressed in Src-deficient cells significantly enhanced phosphorylation of TSC2 in these cells, but it failed to activate the inhibited components of the mTOR pathway that are downstream of TSC2. The data indicate that the Src kinase activity is essential for the activity of mTOR-dependent signaling pathway and suggest that mTOR targets may be controlled by Src independently of Akt1/TSC2 cascade in cells expressing hyperactive Src protein. These observations might have an implication in drug resistance to mTOR inhibitor-based cancer therapy in certain cell types.